Improving microbial growth and biological productions of fermented palm kernel cake through solid state fermentation using Bacillus velezensis with addition of reducing sugar from molasses and nitrogen from urea as supplements - Pongmalai, Patsaporn; Sae-Teng, Apichaya; Rattanakaruna, Saisunee; Yuenyang, Thananon; Siriraksophon, Sunun (Agriculture and Natural Resources, 2025)
Importance of the work: Palm kernel cake (PKC), a by-product from the palm oil industry containing 14-18% protein, is well-known as an alternative protein ingredient to reduce the cost of animal feed. However, the utilization of cellulosic PKC as an animal feed ingredient is still limited. Improving the nutrition value and protein content of PKC via solid state fermentation (SSF) with useful probiotics would benefit more utilization as an ingredient in poultry or monogastric animals. Objectives: The SSF of PKC using Bacillus velezensis, together with adding supplements, was investigated to help increase microbial growth and biological production. Materials and Methods: Suitable conditions for culturing B. velezensis by SSF using PKC as a substrate were investigated with the addition of reducing sugar (RS) from molasses and nitrogen (N) from urea as microbial supplements. The total viable count (TVC), enzyme activities, and protein content of fermented PKC were considered for the conditions selected. Results: From the results, fermentation of PKC with the addition of 20 g RS/kg sample and without N addition for 5 days illustrated high TVC of 10.05 log CFU/g sample (1.16×1010 CFU/g sample), soluble protein content of 17.51 mg/g sample (d.b.) as well as protease and amylase activities of 49.41 and 739.13 U/g sample (d.b.), respectively. Crude protein content by proximate analysis of the fermented samples increased from 13.79% to 20.98% or 1.52-fold higher than that of only PKC, while the crude fiber of the fermented PKC was slightly reduced from 27.11% to 25.40% or decreased by 0.94-fold. Main finding: Fermentation of PKC by SSF using B. velezensis with the addition of RS at 20 g RS/kg sample for 5 days was considered a suitable biological production process to improve microbial growth and the nutrition value of fermented PKC and would be applicable for probiotic production.